Ergonomic challenges in healthcare: mapping physical load during patient transfers using electromyographic field measurements - Jonas Vinstrup; Markus Due Jakobsen; Anders Bruun Nielsen; Lars Louis Andersen; Lars Louis Andersen (Frontiers Media S.A., 2024)
PurposeWork-related musculoskeletal disorders are prevalent among healthcare workers. These workers experience high rates of low-back pain; partly due to the high physical demands of patient transfers. Understanding the specific transfer scenarios that contribute to high physical loads is therefore crucial for developing strategies to improve working conditions.MethodsThis study utilized electromyography to measure muscle activity in the erector spinae muscles during patient transfers, performing measurements in real-life hospital settings to identify the physical load associated with different transfer scenarios. Using linear mixed models, the 95th percentile ranks of the normalized root mean square (nRMS) values were analyzed for a range of different patient transfers.ResultsThe results revealed significant differences in physical load across various patient transfer scenarios. High-load activities included sitting to lying down or lying down to sitting (nRMS 32.7, 95% CI: 28.9-36.6) and lifting the upper body (32.4, 95% CI: 28.8-35.9), while low-load activities such as supporting patients while walking or standing (21.9, 95% CI: 18.6-25.1) and mobilizing in bed (19.9, 95% CI: 16.1-23.8) required less muscle activation. Moderate-load activities included bed to chair transfers (28.1, 95% CI: 24.9-31.3) and lifting the head (26.3, 95% CI: 22.7-29.9).ConclusionUnderstanding the physical load associated with different patient transfer scenarios allows for better organization of work in healthcare settings. These novel findings emphasize the need for effective task allocation, rotational schedules, and the use of assistive devices to distribute physical load and reduce injury risk.